(untitled) (Iraqi Journal of Civil Engineering, 2009)
AbstractSolid waste data survey for the period from 1977 and 2002 has been collected andanalyzed, while the solid waste generated in six regions in Baghdad, which were selectedand estimated to be 1435 houses and 28643 households for the period 2000-2005 wasstudied. The growth of Baghdad’s population, increasing urbanization and rising standardsof living have all contributed to an increase in both the amount and the variety of soliddomestic wastes.The amounts of waste generated and their sources, the type of materials in eachwaste stream, their properties, potential toxicity, and the hazards were evaluated. The lackof reliable time series on solid waste streams and rapid changes in the composition ofwaste streams are a serious impediment to setting priorities in solid waste management inBaghdad. The basic conclusions from this study are:– The waste generated per capita in Rusafa, Kerkh and Baghdad increased from 0.32,0.46 and 0.354 kg/day in 1977 to 0.98, 1.37 and 1.11 kg/day respectively in 2002.- Municipal wastes in Baghdad have a higher proportion of organic matter and ash,higher moisture content and lower paper content. Organic matter and ash may account for between 76-89% of all wastes in low income settlements. Thepercentage of organic waste decreased from 91.17% in 1977 to 64% in 2002, whileplastic, paper, textile, metal, wood and glass wastes increased slightly at the sameperiod.- Collected solid wastes amounts were less than evaluated solid wastes amountsduring the period from 1977 to 2005 because of war and economic sanction.Keyword: SolidWaste management, Waste composition and characteristics, Baghdad city